Mawlana Mawdudi and political Islam : authority and the Islamic state - Jackson, Roy, 1962- (Routledge, 2011)
Mawlana Mawdudi was one of the most influential and important Islamic thinkers of the 20th century. His brand of political Islam has won widespread acceptance in South and South East Asia as well as the Middle East. This text critically engages and assesses his career and legacy.